Potential and Contribution of MICE Service Business Development in South Sulawesi - Syafruddin, Syafruddin (Technium Sustainability, 2021)
The purpose of this study is to determine the potential and contribution of MICE Service Business Development in South Sulawesi. The method of this research is qualitative research. In this research found that in terms of amenities accessibility and attraction for the minimum requirement for MICE activity already fulfilled but still need improvement in order to reach international scale, even during the Covid19 pandemic MICE not proceeded as usual but doesn’t mean the potential doesn’t exist, but it need support from the government in promotion, so far MICE that already proceed has not provided great benefits to the development of marine tourism because MICE haven’t collaborated and innovated that involve the management of marine tourism in South Sulawesi so from here onwards required cooperation and togetherness in every MICE implementation for the activity target as a trigger for developing other tourism businesses can be achieved.